CO2-blown microcellular non-isocyanate polyurethane (NIPU) foams: from bio- and CO2-sourced monomers to potentially thermal insulating materials. Issue 7 (14th December 2015) - Grignard, B.; Thomassin, J.-M.; Gennen, S.; Poussard, L.; Bonnaud, L.; Raquez, J.-M.; Dubois, P.; Tran, M.-P.; Park, C. B.; Jerome, C.; Detrembleur, C.
Abstract : Bio- and CO2 -sourced non-isocyanate polyurethane (NIPU) microcellular foams were prepared using supercritical carbon dioxide (scCO2 ) foaming technology. Abstract : Bio- and CO2 -sourced non-isocyanate polyurethane (NIPU) microcellular foams were prepared using supercritical carbon dioxide (scCO2 ) foaming technology. These low-density foams offer low thermal conductivity and have an impressive potential for use in insulating materials. They constitute attractive alternatives to conventional polyurethane foams. We investigated CO2 's ability to synthesize the cyclic carbonates that are used in the preparation of NIPU by melt step-growth polymerization with a bio-sourced amino-telechelic oligoamide and for NIPU foaming. Our study shows that CO2 is not only sequestered in the material for long-term application, but is also valorized as a blowing agent in the production of NIPU foams. Such foams will contribute to energy conservation and savings by reducing CO2 emissions.